ANALISA KARAKTERISTIK BETON DENGAN VARIAN CANGKANG SAWIT-BATU PECAH - Muhammad Shalahuddin; Alex Kurniawandy; Gussyafri - (Jurnal APTEK, 2013)
Concreteis amixture ofportlandcement,fine aggregate, coarse aggregateand waterwith orwithout additives. Palmshells are hard enough with a lot of surface rupture to beable toreplace thecoarse aggregateonconcreteproperties, especially fornonstructuralconcrete.Combinationof materialconblock concrete of 60 % palm shelland 40% sand using water-cement ratio 0.4 and 0.45 showedstrength 4.0MPa(Muhammad Shalahuddin, 2012).Mixingconcreteis done byDOEmethod,60 samplescylindricaldiameter of 15cm andheight of 30cm. Compressive strengthof concretetestedat 28 dayswith a variety of water-content ratio and a variety of coarse aggregate-palm shells.The greater the percentage of use of the palm shell, made of concrete compressive strength decreases. Concrete compressive strength decreases with increasing of water-content ratio. Variations palm shell 50% and 50% of crushed stone with water-content ratio 0.4 and 0,45 produces compressive strength above 12.5 MPa.